Study on corporate environmental responsibility measurement method of energy consumption and pollution discharge and its application in industrial parks. (1st December 2021) - Han, Xiuyan; Cao, Tianyi
Abstract: The large-scale energy consumption produced by corporates in China's industrial parks has produced a large number of waste discharges. The toxic substances in these wastes have caused a certain degree of environmental pollution, which poses a threat to the living environment, health, and even life of human beings. The measurement method of corporate environmental responsibility and its application, which gradually become a significant issue, have been put forward for improving and solving the increasingly severe environmental pollution problems in industrial parks. Based on the literature review, current situation analysis, and the latest researches, this paper proposes an input-output model considering energy consumption input and unexpected output, improves the input-output model according to the requirements of corporate environmental responsibility measurement, constructs the environmental responsibility improved input-output measurement model of corporate energy consumption and pollution discharge in industrial parks, and selects Nanjing MV Industrial Park as a case to conduct the application test of measuring the corporate environmental responsibility from energy consumption and pollution discharge. The measurement results show that from 2010 to 2018, the responsibilities of energy consumption and environmental treatment, environmental improvement, and the total environment in Nanjing MV Industrial Park have been declining slowly, which shows that the corporate environmental pollution treatment effect of Nanjing MV Industrial Park has been gradually improved. The research results of this paper provide a quantitative analysis method for strengthening the management of corporate environmental responsibility in industrial parks, promoting corporates to strengthen energy conservation and emission reduction, and realizing the sustainable development of industrial parks; for helping the local governments to formulate corporate energy consumption and environmental responsibility management policies in industrial parks and to strengthen the assessment and evaluation of corporate energy consumption and environmental responsibility. Graphical abstract: Image 1 Highlights: Energy Consumption is the Main Cause of China's Environmental Responsibility. This paper uses green input-output model to measure environmental responsibility. Taking Nanjing MV Industrial Park as an example, the application research is carried out. Its research results are the quantitative means of environmental responsibility analysis.